Thermal Evaluation of Brick Wall Configurations Using FEM Simulation and Economic Analysis for Tropical Building Applications - Eva Priyanti; Indra Rio Saputro (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Walls are essential components of the building envelope that regulate heat transfer and influence indoor thermal conditions in tropical buildings. However, the selection of brick wall configurations in Indonesia is generally based on construction cost and conventional practice rather than quantitative thermal performance evaluation. This study aims to evaluate the thermal performance and cost efficiency of commonly used solid clay brick wall configurations and to develop design recommendations based on different levels of solar heat exposure. The study employed thermal resistance (R-value) and thermal transmittance (U-value) calculations, Finite Element Method (FEM) simulations to evaluate temperature distribution and heat transfer behavior, and construction cost estimation through an integrated thermal–economic analysis. Three wall configurations were evaluated: half-brick wall, one-brick wall, and half-brick wall with an air cavity. The half-brick wall exhibited an R-value of 0.17 m²K/W and a U-value of 5.88 W/m²K, representing the lowest thermal resistance but the lowest construction cost (IDR 150,000/m²). The one-brick wall achieved an R-value of 0.34 m²K/W and a U-value of 2.94 W/m²K, with a construction cost IDR 280,000/m². The half-brick wall with an air cavity demonstrated the highest thermal resistance (0.50 m²K/W) and the lowest U-value (2.00 W/m²K), however it required the highest construction cost (IDR 320,000/m²). The findings indicate that the one-brick wall provides the optimum balance between thermal performance and cost efficiency, while cavity walls are recommended for areas exposed to high solar radiation in tropical buildings.